Development of In Vitro Regeneration Protocol for Apple Rootstocks M7 and M9 - Gupta, Nidhi (My University, 2011)
This study was taken up for the in vitro propagation, regeneration and rooting of apple rootstocks M7 and M9. Murashige and Skoog‟s (1962) medium was used throughout the study. Maximum shoot multiplication was achieved when basal medium supplemented with 2.5 μM 6-Benzylamino purine (BAP) and 0.5 μM Naphthalene acetic acid (NAA). Rooting of microshoots was achieved on MS medium supplemented with 5.0 μM IBA. Shoot regeneration was attempted on MS medium supplemented with various concentrations of BAP and 2, 4-dichlorophenoxyacetic acid (2, 4- D) or NAA. Although initially no shoot regeneration occurred but shoots were regenerated when nodular calli developed on MS medium variously supplemented with BAP and NAA. Shoots were cultured on MS medium supplemented with 1.0 – 5.0 μM NAA and 1.0 – 5.0 μM BAP in both rootstocks. Histological analysis of regenerating tissue revealed that the developed structures were shoot buds. The clonal fidelity of regenerated plantlets was established using Random Amplified Polymorphic DNA (RAPD) and Inter Simple Specific Repeats (ISSR) markers.
M.Sc. (Biotechnology)
Keywords: Plant; Tissue; Culture (Apple)